2006
DOI: 10.1111/j.1365-2036.2006.02945.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the opportunities and benefits of extended acid suppression

Abstract: SUMMARYAcid suppression therapy with proton pump inhibitors is associated with well-established benefits in the management of gastro-oesophageal reflux (GERD) and other acid-related disorders. However, a number of issues still remain unsettled. Despite their clinical efficacy, when given once daily, currently available proton pump inhibitors may not adequately control intragastric acidity during the night in a significant proportion of both healthy subjects and GERD patients, in whom symptom relief remains sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 100 publications
(114 reference statements)
0
34
0
2
Order By: Relevance
“…A randomized clinical trial (CT) reported that esomeprazole 80 mg was more effective than lansoprazole 60 mg in maintaining intragastric pH > 4 for > 16 h; the split dose of omeprazole was more effective than the standard dose in maintaining pH control (29). No differences in daytime pH control were observed with different omeprazole dosing regimens (40-0-0, 0-0-40 mg versus 20-0-20 mg) during 7 days (n = 18 healthy subjects); the split dose was superior in controlling nighttime intragastric pH than the standard dose given in the morning or in the night (60 vs. 30 vs. 20%; p = 0,02) (28).…”
Section: How Can the Action Of Ppis Be Modified?mentioning
confidence: 89%
“…A randomized clinical trial (CT) reported that esomeprazole 80 mg was more effective than lansoprazole 60 mg in maintaining intragastric pH > 4 for > 16 h; the split dose of omeprazole was more effective than the standard dose in maintaining pH control (29). No differences in daytime pH control were observed with different omeprazole dosing regimens (40-0-0, 0-0-40 mg versus 20-0-20 mg) during 7 days (n = 18 healthy subjects); the split dose was superior in controlling nighttime intragastric pH than the standard dose given in the morning or in the night (60 vs. 30 vs. 20%; p = 0,02) (28).…”
Section: How Can the Action Of Ppis Be Modified?mentioning
confidence: 89%
“…The potent and long-acting PPI would be feasible for the treatment of gastrointestinal bleeding [Katz et al, 2006;Scarpignato and Pelosini, 2006]. The success rate of Helicobacter pylori eradication therapy depends on intragastric pH, so a long-acting PPI would be acceptable [Katz et al, 2006;Scarpignato and Pelosini, 2006]. Optimizing the control of intragastric pH would also be beneficial in these ARDs, so that a potent and long-acting PPI such as E3710 would be expected to offer improved clinical outcomes for patients with these ARDs as well as GERD.…”
Section: E3710 In the Futurementioning
confidence: 99%
“…The current PPIs are not able to maintain intragastric pH>6 for prolonged periods. The potent and long-acting PPI would be feasible for the treatment of gastrointestinal bleeding [Katz et al, 2006;Scarpignato and Pelosini, 2006]. The success rate of Helicobacter pylori eradication therapy depends on intragastric pH, so a long-acting PPI would be acceptable [Katz et al, 2006;Scarpignato and Pelosini, 2006].…”
Section: E3710 In the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological acid suppression in these diseases, especially in ulcers and GERD, causes very important benefits, such as abolition of elective surgery and reduction in non-steroidal anti-inflammatory drugs-associated gastropaties (Scarpignato and Pelosini, 2006).…”
Section: Introductionmentioning
confidence: 99%